ANALISIS KUALITAS JASA PENDIDIKAN MENGGUNAKAN MODEL SERVQUAL - Sari, Novita (Institut Informatika Dan Bisnis (IIB) Darmajaya, 2015)
As the organizer of higher education, Informatics and Business Institute (IBI) Darmajaya Bandar Lampung continually strive to improve academic quality to convince the public that Darmajaya IBI is committed to providing the best for the education of young generation, especially in Lampung Province. The latest program was established by the IBI Darmajaya is Graduate Master of Information Technology and Master of Management. Various attempts were made by IBI Darmajaya to improve service to graduate students with the building of infrastructure facilities and curriculum. With the advanced elements of quality of service to students as an important indicator of factors, then it is expected to improve performance and competitiveness of graduate programs amid the onslaught of competition IBI Darmajaya colleges in the province of Lampung.This research is descriptive and aims to determine the student responses to the quality of service provided by the organizers of IBI Darmajaya graduate program and to determine the extent of satisfactory service for its students. Samples in this study were graduate students IBI Darmajaya some 71 people with engineering samples using the techniques of sampling using probability sampling with simple random sampling. The method used in this study is SERVQUAL (service quality) to describe the gap and the expected quality of service received by graduate students IBI Darmajaya to determine the level of studentâs satisfaction. Of the gap was then made to determine the Cartesian diagram in which the dimensions of the graduate program of service should be improved or maintained. The result showed that the gap, which indicates that the quality of services not optimally satisfy the students because all gap value â (minus). However, on average, students have felt satisfied with existing services. The implications of the Cartesian diagram, IBI Darmajaya graduate programs need to improve services and maintain the dimension A dimension B because the graduate program has demonstrated outstanding service quality in line with expectations and the reality of services received by7 students.Keywords: SERVQUAL, Gap Analysis, Cartesian diagram, student satisfaction